Revolution Solids in Engineering Course with Matlab (Research, Society and Development, 2017)
This paper aims to present two activities elaborated with the Matlab software on the teaching of Mathematical concepts of Solid of Revolution in the x and y axes, used as pedagogical support tool with students of an Engineering course, complementing the expositive classes on the same subject . The methodology used is of the academic type, seeking to extend the knowledge in the discipline Differential and Integral Calculus regarding the teaching-learning process. Based on the results obtained, we can prove the importance of the use of such a tool in the teaching-learning process because the classroom became a differentiated moment, through the interaction and motivation of the student, who actively participates in his or her learning with better or better use of the lecture.